As construções geométricas e a gênese instrumental: o caso da mediatriz - Jesus, Gilson Bispo de (2012)
This thesis deals with the Instrumental Genesis, which is the preparation process of instrument by the subject. Studies on national and international levels have addressed this process, however, no studies that dealt with Instrumental Genesis referring to an abstract artifact were found. This research revealed the bisector as an abstract artifact. Thus, the goals were to analyze based on the actions of two teachers as the bisector artifact becomes an instrument to solve geometric problems, and investigate how this process could contribute to the learning of geometry by these teachers. Based on these objectives, the research conducted answered the following research questions: how the bisector of Instrumental Genesis happens when the subject interacts with this mathematical object to solve a geometric problem? How the insertion of a bisector mathematical object may interfere in the geometric content learning process by the subject? The methodological choice was the case study that contributed to the achievement of research objectives and the studies those carried out regarding Theory of Instrumentation and Anthropological Theory of Didactics which provided the theoretical elements appropriate for this research. The task, techniques and theoretical-technological discourse analysis enabled to perceive the various instruments developed by teachers while they organized their actions. Furthermore, the didactic organization enabled teachers to develop different techniques supported in the theoretical-technological discourse by solving geometric construction tasks proposed in this organization. The process of Instrumental Genesis of bisector was found in the teachers actions, since these actions emphasized the mobilization and/or construction of various use schemes that were added to this mathematical object. At the same time, this process contributed to the learning mediated by bisector of some topics of Plane Geometry